2009
DOI: 10.14430/arctic7
|View full text |Cite
|
Sign up to set email alerts
|

Bowhead whales, and not right whales, were the primary target of 16th- to 17th-century Basque Whalers in the Western North Atlantic

Abstract: ABSTRACT. During the 16th and 17th centuries, Basque whalers travelled annually to the Strait of Belle Isle and Gulf of St. Lawrence to hunt whales. The hunting that occurred during this period is of primary significance for the North Atlantic right whale, Eubalaena glacialis (Müller, 1776), because it has been interpreted as the largest human-induced reduction of the western North Atlantic population, with ~12 250 -21 000 whales killed. It has been frequently reported that the Basques targeted two species in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 85 publications
1
62
0
Order By: Relevance
“…Reeves et al 1999Reeves et al , 2007, recent data suggest that the observed low genetic variation in the present population may pre-date whaling activities (Waldick et al 2002;Rastogi et al 2004;McLeod et al 2008). Genetic assessment of the contemporary right whale population using nuclear microsatellite markers concluded that a genetic bottleneck has not occurred in the last 200 years (coinciding with the peak of American whaling) and that 800 years of erosion of alleles due to harvesting may be responsible for the low variability in this species (Waldick et al 2002).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Reeves et al 1999Reeves et al , 2007, recent data suggest that the observed low genetic variation in the present population may pre-date whaling activities (Waldick et al 2002;Rastogi et al 2004;McLeod et al 2008). Genetic assessment of the contemporary right whale population using nuclear microsatellite markers concluded that a genetic bottleneck has not occurred in the last 200 years (coinciding with the peak of American whaling) and that 800 years of erosion of alleles due to harvesting may be responsible for the low variability in this species (Waldick et al 2002).…”
Section: Introductionmentioning
confidence: 87%
“…Because the historic bone specimen possessed a mitochondrial control region haplotype different from those found in the extant population (haplotype 'F'; AY821863; Rastogi et al 2004), the purity of each DNA extraction (n = 8) was assessed by amplifying and sequencing 218 bp of this fragment using primers UP098 and LP282 (Rastogi et al 2004). PCR conditions followed that of McLeod et al (2008) and included 5 ll DNA extract. PCR product was purified and sequenced as per McLeod et al (2008) and then compared to the six known E. glacialis haplotypes Rastogi et al 2004) (Genbank Accession numbers AF395039-AF395043, AY821863).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subfossil baleen whale samples were sampled following the protocol outlined in McLeod et al 20 , from collections held at the Zoological Museum, University of Copenhagen; Natural History Museum, Rotterdam; Gothenburg Museum of Natural History; Gothenburg Stadsmuseum; Vendsyssel Historical Museum; Museumcenter, Hanstholm; and Natural History Museum of Aarhus. Previous genetic studies have shown that bowhead whale B. mysticetus and right whale E. glacialis skeletal remains cannot always be reliably distinguished based on morphology 24 . Given that many of our samples were from vertebrae, from which curators suggested they could not conclusively distinguish among taxa, species identification was molecularly determined using aDNA protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we use aDNA to verify the species identification of subfossils catalogued as bowhead whales based on morphology, but which could be right whales given their southerly distribution and the difficulty in distinguishing between the two taxa based on some morphological traits 24 . We model the distribution of the preferred habitat of the bowhead whale during the Late Pleistocene using paleoclimate data from the Last Glacial Maximum to investigate if the distribution of bowhead whale subfossils matched the predicted range.…”
mentioning
confidence: 99%